Genomic characterization of H14 subtype Influenza A viruses in new world waterfowl and experimental infectivity in mallards (Anas platyrhynchos). - Andrew M Ramey; Rebecca L Poulson; Ana S González-Reiche; Daniel R Perez; David E Stallknecht; Justin D Brown (PLoS ONE)
Recent repeated isolation of H14 hemagglutinin subtype influenza A viruses (IAVs) in the New World waterfowl provides evidence to suggest that host and/or geographic ranges for viruses of this subtype may be expanding. In this study, we used genomic analyses to gain inference on the origin and evolution of H14 viruses in New World waterfowl and conducted an experimental challenge study in mallards (Anas platyrhynchos) to evaluate pathogenicity, viral replication, and transmissibility of a representative viral strain in a natural host species. Genomic characterization of H14 subtype IAVs isolated from New World waterfowl, including three isolates sequenced specifically for this study, revealed high nucleotide identity among individual gene segments (e.g. ≥95% shared identity among H14 HA gene segments). In contrast, lower shared identity was observed among internal gene segments. Furthermore, multiple neuraminidase subtypes were observed for H14 IAVs isolated in the New World. Gene segments of H14 viruses isolated after 2010 shared ancestral genetic lineages with IAVs isolated from wild birds throughout North America. Thus, genomic characterization provided evidence for viral evolution in New World waterfowl through genetic drift and genetic shift since purported introduction from Eurasia. In the challenge study, no clinical disease or lesions were observed among mallards experimentally inoculated with A/blue-winged teal/Texas/AI13-1028/2013(H14N5) or exposed via contact with infected birds. Titers of viral shedding for mallards challenged with the H14N5 IAV were highest at two days post-inoculation (DPI); however shedding was detected up to nine DPI using cloacal swabs. The distribution of viral antigen among mallards infected with H14N5 IAV was largely restricted to enterocytes lining the villi in the lower intestinal tract and in the epithelium of the bursa of Fabricius. Characterization of the infectivity of A/blue-winged teal/Texas/AI13-1028/2013(H14N5) in mallards provides support for similarities in viral replication and shedding as compared to previously described waterfowl-adapted, low pathogenic IAV strains in ducks.